International organisations on national politics: Council of Europe effects on political party in Turkiye - Kahraman, Selçuk; Kutlu, Önder (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
This paper intends to examine influence of the Council of Europe (CoE) in two major political parties of Turkiye through their election manifests during the first quarter of the 21st century. The ruling AK Parti and main opposition party, CHP, election manifests are reviewed via MAXQDA data analysis panel. As one of the founding member states of the Council Turkiye has got close ties with the organisation and this has impositions on the national politics. This being the case, the problem of how this area is put on the agenda and evaluated in terms of Turkish political life becomes important. The effects of the CoE on Turkish political parties are classified under eight headings. These headings are examined with the help of graphics as 8 subcategories: “law”, “fundamental rights and freedoms”, “foreign policy”, “public administration”, “fight against corruption”, “democracy”, “labour and social security” and “family and social policies”. Among these, “law” and “fundamental rights and freedoms” categories stand out as the most emphasized issues in the context of the CoE for both parties. Finally reveals that CHP and AK Parti priorities or emphases diverge on certain issues related to CoE. Thus, family and social policies for the CHP, and foreign policy and the fight against corruption for the AK Parti have defined the more prominent categories. Having examined the effects of the Council the paper draws a clear line of relations as far as the eight categories are concerned.